2020
DOI: 10.1016/j.apm.2019.09.014
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the one-dimensional Euler–Lagrange equation of continuum mechanics with a Lagrangian of a special form

Abstract: Flows of one-dimensional continuum in Lagrangian coordinates are studied in the paper. Equations describing these flows are reduced to a single Euler-Lagrange equation which contains two undefined functions. Particular choices of the undefined functions correspond to isentropic flows of an ideal gas, different forms of the hyperbolic shallow water equations. Complete group classification of the equation with respect to these functions is performed.Using Noether's theorem, all conservation laws are obtained. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(37 citation statements)
references
References 31 publications
1
33
0
Order By: Relevance
“…In [22] the group classification of the one-dimensional Euler-Lagrange equations of continuum mechanics was carried out by the authors. In particular, it was shown that the modified shallow water equation ( 7) is the Euler-Lagrange equation for the Lagrangian…”
Section: Symmetries and Conservation Laws In Lagrangian Coordinatesmentioning
confidence: 99%
See 3 more Smart Citations
“…In [22] the group classification of the one-dimensional Euler-Lagrange equations of continuum mechanics was carried out by the authors. In particular, it was shown that the modified shallow water equation ( 7) is the Euler-Lagrange equation for the Lagrangian…”
Section: Symmetries and Conservation Laws In Lagrangian Coordinatesmentioning
confidence: 99%
“…One can find a more detailed discussion of the symmetries and conservation laws of the modified shallow water equations with different bottom topographies in [22].…”
Section: Symmetries and Conservation Laws In Lagrangian Coordinatesmentioning
confidence: 99%
See 2 more Smart Citations
“…Group properties of the two dimensional gas dynamics equations of a polytropic gas in mass Lagrangian coordinates were analyzed in [4]. It should be also noted the paper [6], where flows of one-dimensional continuum in Lagrangian coordinates are considered. Equations describing these flows are reduced to a single Euler-Lagrange equation which contains two undefined functions.…”
Section: Introductionmentioning
confidence: 99%